Promise and Pitfalls in the Use of “Secondary” Data-Sets: Income Inequality in OECD Countries as a Case Study - Atkinson, Anthony B; Brandolini, Andrea (Journal of Economic Literature, 2001)
This paper examines the role of secondary data-sets in empirical economic research, taking the field of income distribution as a case study. We illustrate problems faced by users of “secondary” statistics, showing how both cross-country comparisons and time-series analysis can depend sensitively on the choice of data. After describing the genealogy of secondary data-sets on income inequality, we consider the main methodological issues and discuss their implications for comparisons of income inequality across OECD countries and over time. The lessons to be drawn for the construction and use of secondary data-sets are summarized at the end of the paper.